PENGARUH TINGKAT PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI SUMATERA SELATAN TAHUN 2010-2020 - Rohmatun Hasanah; Maya Panorama (JEP (Jurnal Ekonomi Pembangunan), 2021)
This study aims to determine how much influence the unemployment rate has on the poverty rate in South This study aims to determine how much influence the unemployment rate has on the poverty rate in South Sumatra from 2010 to 2020. The data used in this study is secondary data. The data was obtained from published data from the Statistics Agency (BPS). This study uses quantitative methods. The analytical technique used in this study is a simple regression analysis using Eviews 11. The results show that the unemployment rate variable has a positive and significant effect on the poverty rate in South Sumatra in 2010-2020 as seen from the t count > t table (2.89 > 1.81) with probability 0.0180 < 0.05.